GIS-based Accessibility Analysis Using Suitable Land for Public Parks in Larkana City Pakistan - Matori, A.N (Maxwell Science Publication, 2011)
Land-use plays an important role in social, cultural and physical development of human beings. A variety of recreational activities creates conducive living environment for humans. Accessibility is significant for land-use planning and use of suitable land for development. Uncontrolled expansion and unauthorized development has created serious urban environmental problems due to urban facilities extension. This fact affects the social behavior and physical development of residents. The aim of this study is to get a better urban environmental benefits and accessibility to parks by the inhabitants of the Larkana city. In finding the suitable land, geographic information system was adopted. Weighted model was integrated in GIS by using Analytical Hierarchy Process (AHP) in finding the suitable land. Based on suitability map, the Euclidean-allocation model was applied to determine the accessibility using GIS spatial analysis function of the ArcGIS software. The results of this study revealed that it is not enough only finding suitable land for allocation of facilities, whilst neglecting how these facilities should be accessed. Therefore, GIS spatial analysis technique is the viable method to analyze service area’s parks accessibility facilities